Management of scarce water resources : a Middle Eastern experience - El-Naser, H. (Hazim) (Southampton ; Boston : WIT Press, 2009)
'Arid and semi-arid countries have historically suffered from a plethora of complex water concerns due to its climatic limitations. Research in these regions has long supported the necessity of delivering life sustaining access and availability to water while being inherently linked to several inter-related factors, including technical and economic issues, human resources, health and private sector participation. Regional conflicts and controversial political agendas have also exercised a profound impact on the viability of co-operative water resource and management perspectives.'--Back cover.
Scarce water countries -- Regional water resources: conflicts and prospects -- Water management and sustainable development -- Groundwater use and management -- Online sources and tools.
Includes bibliographical references (p. 193-198) and index.
Keywords: Water conservation -- Middle East; Water-supply -- Middle East -- Management; Water-supply -- Middle East -- Case studies; Water-supply -- International cooperation